Threshold‐based context analysis approach for ubiquitous systems. (11th June 2013) - Khabou, Nesrine; Rodriguez, Ismael Bouassida
Summary: In ubiquitous computing environments, applications must be able to respond to dynamic context changes in order to provide suitable services to users. A promising solution consists of developing context aware applications. In this paper, we present an approach that supports context awareness in a ubiquitous computing environment. The proposed approach focuses on handling context information including context monitoring/acquisition, context interpretation, context classification, context storage, context analysis, and context aware adaptation. In this paper, we focus on context classification and context analysis. We present a context classification approach, which takes into account the context parameter evolution behavior. Then, we define a context analysis approach for ubiquitous computing environments. The proposed analysis approach aims at analyzing contextual information and detecting significant changes. The proposed analysis approach uses a threshold comparison technique in order to detect context changes. When relevant context changes are detected, the context aware application will be notified to trigger its suitable process dynamically in order to deal with the changes. Copyright © 2013 John Wiley & Sons, Ltd.